Viscosity and oxidative stability of copper (II) oxide nanofluid dispersed in sunflower oil / Azmi Roslan ...[et al.] - Roslan, Azmi; Arif Rasul, Muhammad; Othman, Saziman; Zolkepli, Nurul Afifah
Nanofluid is a substance that containing nanoparticle which has the unique make them potentially useful in many applications in heat transfer. Nanoparticle has started to play an important role as lubricant additive for their potential in emissions reduction and improving fuel economy. The nanoparticle that usually used in nanofluids is typically made from metal, oxide, and carbides, or carbon nanotubes. The purpose of these experiments is to identify the effects of copper (II) oxide nanoparticle to viscosity and oxidation induction time for Sunflower Oil. In this experiment, six samples were prepared with different volume percent of 0.001, 0.002, 0.003, 0.004 and 0.005 in sunflower oil and one sample act as a reference (0% Copper (II) Oxide). The experiment for viscosity test was conducted by using Rotational Brookfield Viscometer DV2T and the type of spindle to perform in this experiment is L V-62. It was tested at the different speed from 60 RPM to 200 RPM with I 0RPM increment every 5 minutes run. The number of absolute viscosity ( cP avg) will be calculated to take the average before plot the data results. The experiment for oxidation induction time was conducted by using DSC software program. The conclusion from the result of an experiment of viscosity test shows that 0.005 of volume percent of mixture copper(II) oxide · nanoparticle and sunflower oil have the highest viscosity compared to others. From this experiment, the samples show that base fluid contained the copper (II) oxide nanoparticle additive are Newtonian fluid. From the oxidation stability experiment, it can be concluded that it does not give any effects if the time increasing when the copper (II) oxide nanoparticle was added to the sunflower oil.